The return of polyandry : kinship and marriage in central Tibet - Fjeld, Heidi (New York : Berghahn Books, 2022)
"Tibet is known for its broad range of marriage practices, particularly polyandry, where two or more brothers share one wife. With economic development and massive Chinese social and political reforms, including new marriage laws prohibiting plural marriages, polyandry was expected to disappear from Tibetan social lives. This book describes the surprising increase in polyandry in Panam valley during the 1980s. It explores married lives in polyandrous houses and develops a theory of a flexible kinship of potentiality through the lens of a farming village in Tibet Autonomous Region. It is the first book-length ethnography to explore kinship and marriage in Tibet under Chinese rule"--
Introduction -- The return of polyandry -- Trajectories into houses -- Fraternal relations -- Female roles -- The house as ritual space -- Moral networks and enduring hierarchies -- Conclusion -- Epilogue -- Appendix. Timeline -- Glossary of Tibetan terms.
Julkaistu myös painettuna.
Kuvailun perustana verkkoaineisto; nimeke PDF-nimiösivulta (katsottu 3.3.2023).
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Marriage customs and rites -- China -- Tibet Autonomous Region; Tibetans -- Marriage customs and rites; Polyandry -- China -- Tibet Autonomous Region; Kinship -- China -- Tibet Autonomous Region; sukulaisuus; avioliitto; polyandria; koti; tiibetiläiset; släktskap; äktenskap; polyandri; hem (boende); tibetaner; Tiibet; Tibet